Improving Language Feature Understanding of Story on Video Through Developing Moodle-Based E-Learning - Antoni, Nur; Kurniawan, Asep (Journal of Nonformal Education, 2022)
In this pandemic situation, English learning mostly has been done online. Hence it’s tutor job to be creative.  Moodle based e learning hoped give  solution.This study has purpose to: (1) produce an appropriate Moodle-based English e-learning product in improving language features of story understanding at Jovelin Course (2) find out how effective Moodle-based e-learning is on language features of story understanding at Jovelin Course. This research uses Research Development. Data collection instruments are interviews, questionnaires, and tests. The following is the study's findings. (1) An online Learning Management System (LMS) based on the Moodle application software version 3.1 was used to produce the e-learning offering. (2) Based on media expert validation with a score of 3.68 with "good" criteria, material expert validation with an average score of 4.29 with "very good" criteria, and user responses with a score of 4.28 with "very good" criteria, Moodle-based e-learning products were declared eligible as learning media. (3) The use of e-learning improved the learning results of Intermediate Level Jovelin Course Brebes students. The rise in learning outcomes, as measured by the percentage of pretest and postest, demonstrates the efficiency of the product for learning English in the capacity of recognizing linguistic aspects of tale on video. Keywords: e-learning, Moodle Based, language features of English.